The Role of Husband in Assisting Wife Who Suffer Anemia in Pregnancy (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Problem in anemia which is commonly suffered by pregnant women is iron deficiency due to unbalanced nutrition. A qualitative research with Ethnomethodology approach. Participants were pregnant women who are anemic with Hemoglobin levels (Hb) less than 11g/dl. 38 of participants consisting of 19 husbands as focus groups and 19 wives as triangulation group obtained through purposive sampling technique. Data obtained through the method of focus groups discussion and in-depth interview, analyzed using descriptive analysis techniques.The result showed that the husband’s role in assisting the wife who suffered from anemia in pregnancy is lacking due to lack of husbnd knowledge about anemia, its causes and how to deal with anemia in pregnancy. The conclusion is the role of husband in assisting wife in pregnancy should be supported with husband’s good knowledge about anemia, its causes and how to deal with anemia in pregnancy in order to prevent anemia in their wives’ pregnancies.